Cylindrical Spirals in Skeletal Muscles Originate From the Longitudinal Sarcoplasmic Reticulum. Issue 2 (February 2016) - Xu, Jing-Wen; Liu, Fu-Chen; Li, Wei; Zhao, Yu-Ying; Zhao, Dan-Dan; Luo, Yue-Bei; Lu, Jian-Qiang; Yan, Chuan-Zhu
Abstract : Cylindrical spirals (CSs) are rare but distinct subsarcolemmal accumulations in skeletal muscle fibers. To date, CSs have been reported in only 16 patients with a variety of neuromuscular conditions. The origin and composition of CSs are unknown, although there are some morphologic similarities between CSs and tubular aggregates (TAs). To clarify the nature of CSs, we characterized the sarcoplasmic reticulum (SR) and other intracellular membrane system proteins in CSs of muscle biopsies from 2 adult Chinese siblings. Immunohistochemical studies revealed subsarcolemmal immunoreactivity for sarco/endoplasmic reticulum Ca 2+ -ATPase 1 (SERCA 1) in the longitudinal SR, but no immunoreactivity for calsequestrin in the terminal cisternae or type 1 ryanodine receptor (RYR1) in the junctional SR. Muscles biopsied from 2 patients with TAs showed immunoreactivity not only for SERCA1 but also for other SR proteins, including calsequestrin and RYR1. CSs exhibited no immunoreactivity for the Golgi apparatus marker GM130, the nuclear membrane emerin, desmin, the autophagosome marker LC3, the lysosomal membrane marker LAMP2, dystrophin, or myosin. Our results suggest CSs may originate only from the longitudinal SR, whereas TAs are composed of both the junctional and longitudinal SR. Immunochemical staining with antibodies against calsequestrin and RYR1 help to distinguish these 2 pathological alterations.